High-frequency equipment inhibition of multidrug-resistant Pseudomonas aeruginosa strain - Gonçalves, Davi; Azevedo, Jailton; Luana Leandro Gois; Paulo Fernando de Almeida; Josilene Borges Torres Lima Matos; Gustavo Miranda Pires Santos (Revista de Ciências Médicas e Biológicas, 2025)
Aim: The emergence of antibiotic resistance, mainly due to misuse of antibiotics, has brought forth the need for studies on new approaches to the treatment of bacterial infections and the decontamination of surfaces. High-frequency equipment has been shown to have antibacterial effects due to the formation of ozone during sparking. This method relies on oxidative damage, which could be less effective in strains adapted to resist antibiotics and oxidative agents such as those used in hospital settings. The aim of this study is therefore to evaluate the efficacy of this technique against clinically isolated multidrug-resistant (MDR) or extensively drug-resistant (XDR) Pseudomonas aeruginosa. Methods: A clinically isolated XDR P. aeruginosa strain and a standard ATCC (American Type Culture Collection) 27853 strain, were spread-plated, divided into three groups, and treated with high-frequency equipment for 0, 5, and 10 minutes prior to incubation. Inhibition was measured through ImageJ, and statistical analysis was performed using GraphPad Prism through ANOVA with Tukey post-test, considering p<0.05 as statistically significant. Results: Both strains were successfully inhibited using high-frequency equipment for exposure times of 5 and 10 minutes (p-value < 0.05). Between 47.2% and 61.44% of the surface area covered by the electrode was inhibited. No differences were found between exposure times (5 and 10 minutes) or resistance profiles. Conclusion: XDR P. aeruginosa strain resistance mechanisms do not seem to impact its susceptibility to high-frequency treatment, as it was equally inhibited compared to a standard ATCC strain. Significant inhibition was detected after only 5 minutes of exposure.